Perception of MBBS, BDS & Nursing Students and Nurses on Lifestyle Medicine and Preventive Healthcare: A Cross-Sectional Study in Four Tertiary Hospitals of India - Sharma, Pravin; Verma, Ishita; Kumar Kantibhai, Bhandari Monik; Devdhar, Saumya; Vanshika, Vanshika; Chaudhary, Varsha; Kumar Garg, Hemant; Mohan, Col. Brij (Journal of Neonatal Surgery, 2025)
Background: Lifestyle medicine and preventive healthcare are critical in reducing the burden of non-communicable diseases (NCDs). Understanding perceptions among healthcare trainees and professionals is essential for curriculum and practice development. Objective: To assess perceptions of MBBS students/interns, BDS students, and nurses regarding lifestyle medicine and preventive healthcare in four tertiary hospitals in India. Methods: A cross-sectional survey was conducted among 250 participants (100 MBBS students/interns, 50 BDS students, 100 nurses). A 15-item Likert-scale questionnaire assessed awareness, attitudes, and perceived importance of lifestyle medicine. Descriptive and comparative analyses were performed. Results: MBBS students demonstrated the highest awareness (78%), followed by BDS students (62%) and nurses (55%). Preventive healthcare was rated “very important” by 85% of MBBS students, 72% of BDS students, and 68% of nurses. Nurses highlighted barriers such as workload and patient compliance. Conclusion: While lifestyle medicine is perceived as important across groups, awareness and emphasis vary. Integration into curricula and interprofessional training is recommended